PENGARUH MANAGERIAL COMPETENCY DAN LEARNING ORIENTATION TERHADAP JOB PERFORMANCE MELALUI ENTREPRENEURIAL LEADERSHIP PADA UNIVERSITAS NEGERI SURABAYA - Hafizh Amrullah (Jurnal Ilmu Manajemen, 2021)
Higher education seeks to maximize managerial competence and learning orientation in job performance. Higher education requires efforts to improve work performance to develop and progress. To achieve this, universities need to strengthen successful entrepreneurial leadership in running organizations to create a better learning atmosphere. This study aims to determine the effect of managerial competence and learning orientation on job performance through entrepreneurial leadership. The respondents are 50 leaders in a higher education institution. Hypothesis testing using Structural Equation Model (SEM) and analysis method using Partial Least Square (PLS). The study results reveal that managerial competence can positively influence job performance. Learning orientation has a positive effect on job performance. Learning orientation has a positive impact on job performance through entrepreneurial leadership. Furthermore, managerial competence positively impacts job performance through entrepreneurial leadership. This study provides significant implications for theories and investigations of strengthening university leadership and provides evidence on how such leadership has significance for good job performance.